Ecotourism Engagement and Community Wellness: The Moderating Role of Cultural Factors in SVD Laudato Si’ Farm, Tagaytay - Bobadilla, Shane; Arintoc, Alyssa Mae; Caromayan, Cristine; Celindro, Jeremy Joshua; Paraiso, Karylle; Pascual, Merlyn; Sulbuan, April Abby; Bayabay, Kathline Mae; Comiso, Aljevin; Arcadio, Anderson Ray (Journal of Interdisciplinary Perspectives, 2025)
Despite the growing popularity of eco-tourism, limited research examines how it contributes to community well-being when cultural factors are considered. This study aimed to investigate the relationship between eco-tourism engagement and community well-being, and to determine whether cultural factors influence this relationship. A quantitative correlational design was employed, involving 317 tourist respondents at SVD Laudato Si’ Farm in Tagaytay, selected through simple random sampling. Data were analyzed using descriptive statistics, Pearson correlation, regression, and moderation analysis. The findings revealed high levels of eco-tourism awareness and participation, along with strong perceptions of physical and mental well-being among the respondents. Results further indicated a significant positive correlation between eco-tourism engagement and community wellness. Moderation analysis revealed that traditions slightly weakened this relationship, while beliefs and community values showed no significant moderating effects. The study concludes that eco-tourism enhances community wellness when it aligns with local cultural contexts. These findings underscore the importance of culturally grounded and inclusive eco-tourism initiatives to foster both community health and heritage preservation.